The clinical role of blood coagulation and platelet receptors gene allelic variants in development of Wilson’s disease - T. P. Rozina; S. V. Fastovets; E. E. Starostina; L. M. Samokhodskaya; T. N. Krasnova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To estimate the effect of carriage of various allelic variants of blood coagulation system and platelet receptors genes on Wilson’s disease (WD) clinical presentation features. Material and methods. Original study included 85 patients with a Wilson’s disease who were divided into two groups: without neurological symptoms (abdominal form; n=51) and with neurologic symptomatology (mixed form; n=34). Genetic polymorphism testing was carried out by real-time polymerase chain reaction with melting curve analysis. Results. Alleles A of hemostasis genes FII 20210 G/A, FV 1691G/A were more frequent in the group with neurologic symptomatology as compared to the group of patients with abdominal form of WD at the level of trend. Frequency of 5G allele of plasminogen activator inhibitor gene PAI-675 5G/4G in the group with neurologic symptoms was lower (41.17%), than in the group without symptoms of central nervous system (CNS) involvement (49.02%) (odds ratio - OR: 1.374; 95% confidence interval - CI: 0.739-2.553). In the group of patients with neurological symptoms 4G4G genotype of PAI-675 5G/4G gene was more common (47.06%), than in patients without those symptoms (23.53%) (OR: 2.889; 95%-CI: 1.135-7.350). The allele T of platelet receptor gene ITGA2 807 C/T was more common in patients with CNS involvement than in the group of patients without neurological symptoms (р =0.018; OR: 2.172. 95%-CI: 1.163-4.058). Integrated genotype CT+TT was significantly more common in patients with neurological symptoms (82.35%) as compared to patients without those (54.90%) (р =0.010; OR: 3,833; 95%-CI: 1.355-10.846). Conclusion. Carriage of mutant genotypes FII 20210 G/A, FV 1691G/A, PAI-675 5G/4G, ITGA2 807 C/T is the factor associated to the presence of neurological symptoms at Wilson's disease.